11. EFFECTIVENESS OF CERVICAL SPINE PAIN RELIEF USING LASER ACUPUNCTURE COMBINED WITH EXERCISE THERAPY IN PATIENTS WITH CERVICAL SPONDYLOSIS (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness and safety of laser acupuncture combined with exercise therapy in patients with cervical spondylosis.Subjects and Methods: A clinical trial was conducted to compare the effectiveness before and after treatment in 30 patients diagnosed with cervical spondylosis. All patients received a combination of laser acupuncture and exercise therapy for 4 weeks. The effectiveness was assessed using the Visual Analog Scale (VAS) for pain.Results: After 4 weeks of treatment, the total VAS pain score decreased by 2.5 points from 5.5 to 3 (p < 0.05). The pain levels according to the VAS scale were: Moderate pain 30%, mild pain 60%, and no pain 10% (p < 0.05). No side effects of laser acupuncture were recorded during the treatment process.Conclusion: The combination of laser acupuncture and exercise therapy is effective in reducing cervical spine pain in patients with cervical spondylosis.
Keywords: Laser acupuncture, exercise therapy, cervical spondylosis